2015
DOI: 10.1002/ajoc.201500475
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox α‐Allylation of α‐Halocarbonyls with Allylboron Compounds Accelerated by Fluoride Salts under Visible Light Irradiation

Abstract: Organicd yes are an attractive alternative to the use of transition-metalc omplexes in photoredox catalysis. Herein, we report an inexpensive organic dye (eosin Y)catalyzed radical coupling of a-bromocarbonyl compounds with allyltrifluoroborates under visible light irradiation. This reactionw as accelerated by either Bu 4 NF or CsF.B ased on mechanistic studies, the cation exchange between potassium allyltrifluoroborate and Bu 4 NF proceeded to generate KF.T he generatedK Fo rC sF acts as aL ewis acid to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…In 19 F NMR (376 MHz, DMSO-d6) δ -136.3 (qua, J = 63.9 Hz, BF3K). The data match with the previously described compound [43,44].…”
Section: General Procedures For the Synthesis Of Potassium (Z) And (E)supporting
confidence: 69%
“…In 19 F NMR (376 MHz, DMSO-d6) δ -136.3 (qua, J = 63.9 Hz, BF3K). The data match with the previously described compound [43,44].…”
Section: General Procedures For the Synthesis Of Potassium (Z) And (E)supporting
confidence: 69%
“…Recently, Yasuda and coworkers developed allyltrifluoroborate as a new‐type allylation reagent for α‐allylation of carbonyl compounds using eosin Y as photocatalyst (Scheme 1(b)). 10 Our research group is interested in using organosilicon groups in photoredox catalysis and recently, we developed organosilicon groups as radical precursors in photocatalytic reactions 11 . Also, we investigated the potential use of allyltrimethylsilane as a novel allylation reagent for α‐allylation of carbonyl compounds because of its neutral, stable, and nontoxic nature.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we observed that the optimization conditions of the reaction of 2-bromoacetophenone 1a with three equivalents of allyltrimethylsilane 2a in the presence of 1.0 mol% of fac-Ir(ppy) 3 in 0.5 M of acetonitrile at room temperature irradiated at 10 W blue LEDs under an argon atmosphere produced the desired products 3a with 80% yield (Table 1, entry 1). The control experiments revealed the essential role of the visible light photoredox catalyst in the reaction (Table 1, entries [10][11].…”
mentioning
confidence: 99%
“…When the reaction using eosin Y (5 mol %) and CsF (3 equiv) was carried out in DMF under visible‐light irradiation by blue LED (468 nm), the allylation product 3 aa was not observed (Table , entry 1). This was the condition for our previously reported system of α‐allylation for α‐bromoketones via allylboron compounds . However, the conditions in the absence of CsF gave 3 aa in a moderate yield of 54 % (entry 2).…”
Section: Methodsmentioning
confidence: 67%